2021
DOI: 10.1186/s13613-021-00868-8
|View full text |Cite
|
Sign up to set email alerts
|

Specific exposure of ICU staff to SARS-CoV-2 seropositivity: a wide seroprevalence study in a French city-center hospital

Abstract: Background Most hospital organizations have had to face the burden of managing the ongoing COVID-19 outbreak. One of the challenges in overcoming the influx of COVID-19 patients is controlling patient-to-staff transmission. Measuring the specific extent of ICU caregiver exposure to the virus and identifying the associated risk factors are, therefore, critical issues. We prospectively studied SARS-CoV-2 seroprevalence in the staff of a hospital in Lyon, France, several weeks after a first epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This nding was consistent with Mascola J. et al and Vivier E. et al, reported similar results. [21], [22] Our study also showed that the ICU HCWs had the highest seroprevalence (27.4%) and the highest odds of having COVID-19 antibodies compared to the hospital and PHC HCWs. Several international studies found a signi cantly higher probability of antibodies among HCWs from high-risk departments.…”
Section: Discussionsupporting
confidence: 60%
“…This nding was consistent with Mascola J. et al and Vivier E. et al, reported similar results. [21], [22] Our study also showed that the ICU HCWs had the highest seroprevalence (27.4%) and the highest odds of having COVID-19 antibodies compared to the hospital and PHC HCWs. Several international studies found a signi cantly higher probability of antibodies among HCWs from high-risk departments.…”
Section: Discussionsupporting
confidence: 60%
“…Intensive care unit (ICU) staff have witnessed the unpredictable course of COVID-19, rapid deterioration of patients’ health, infections among colleagues due to the higher rates of transmission, and long-standing contact and exposure with infected patients daily [ 6 ]. These factors may render them a vulnerable population to perceive more stress and develop PTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased knowledge on the virus transmission mechanisms and systematic use of PPE, by approaching each patient, might feel frontline HCW less exposed to SARS-CoV-2 than second-line HCW. Furthermore, previous studies reported lower SARS-CoV-2 seroprevalence in intensive care units dedicated to CoViD-19 patients [20,21]. Employees classified in higher-risk categories were more likely to lose their motivation, compared to lowrisk, in bivariate analysis.…”
Section: Discussionmentioning
confidence: 79%